Implications of Amending the 1945 Constitution on the Unclear Direction of Constitutional Substance - Benyamin Tungga; Cokorde Wife Dian Laksmi Dewi (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze the Implications of Amending the 1945 Constitution on the Unclear Direction of Constitutional Substance. This study uses normative juridical research methods using secondary data from primary, secondary and tertiary legal materials. The survey results show that radical changes to the provisions of the articles in the 1945 Constitution have resulted in more precise directions for the substance of the constitution. Some things that have become blurred due to the amendment are the parliamentary system between soft or firm bicameral and checks and balances between the executive and the legislature, which need to be balanced. Furthermore, if what is adopted is a two-chamber representative system, then a half-hearted positioning of the authority of the Regional Representatives Council (DPD) is not appropriate. Therefore, it is necessary to redesign the scenario by giving full authority to the DPD. That is, bearing in mind that the development of regional aspirations is running so quickly and rapidly, which must always be. Apart from that, the people's representation system adopted by the new 1945 Constitution is not unicameral because the DPD is a forum for regional representation besides the DPR is a forum for population representation. Still, it is also not bicameral because the bill only requires agreement between the DPR and the President and shifting the Sovereignty of the People to just Sovereignty of Law.